Analysing and Designing Circular Value Networks for Sustainable Tourism – a Case Study (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This exploratory study addresses the lack of literature on circular value networks in sustainable tourism ecosystems. The authors argue that circular, cross-industrial value networks can optimize the use of both tangible and intangible resources within a tourism region, fostering sustainable development. This is particularly relevant given tourism's significant CO2 emissions and its role in addressing SDGs such as goals 3 (good health and well-being), 8 (sustainable economic growth), and 12 (sustainable consumption and production). The central research questions are: “How can unused regional resources in a tourism context be valorised?” and "How does integrating circular value networks in a tourism destination contribute to sustainable development?" Using systemic design methodology (Battistoni et al., 2019), the researchers identify unused resources and existing and potential cross-industrial circular value networks in the Regional Nature Park Pfyn-Finges in the canton of Valais, Switzerland. They analyse selected value networks, examining their potential, challenges, and impact on all three dimensions of sustainability, and design ideal value networks based on these findings. The study highlights the significant potential of unused resources to enhance circular multi-actor value networks within a tourism destination, contributing to all aspects of sustainability and boosting the destination's resilience.